2022
DOI: 10.1021/acs.langmuir.1c03275
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Stabilized Diblock Copolymer Nanoparticles Enable Convenient Preparation of Suspension Concentrates Comprising Various Agrochemical Actives

Abstract: It is well known that sterically stabilized diblock copolymer nanoparticles can be readily prepared using polymerization-induced self-assembly. Recently, we reported that such nanoparticles can be employed as a dispersant to prepare micron-sized particles of a widely used fungicide (azoxystrobin) via ball milling. In the present study, we examine the effect of varying the nature of the steric stabilizer block, the mean nanoparticle diameter, and the glass transition temperature ( T g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Optical microscopy studies confirmed a substantial reduction in mean particle size (Figures 9a and 9b) while laser diffraction studies indicated that the final azoxystrobin microparticles had a mean diameter of 2.0 μm (Figure 9c). These observations are very similar to those obtained when using non‐degradable methacrylic nanoparticles as a dispersant [10,11] . In principle, such hydrolytically degradable nanoparticles could be used to prepare more environmentally‐friendly next‐generation agrochemical formulations.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Optical microscopy studies confirmed a substantial reduction in mean particle size (Figures 9a and 9b) while laser diffraction studies indicated that the final azoxystrobin microparticles had a mean diameter of 2.0 μm (Figure 9c). These observations are very similar to those obtained when using non‐degradable methacrylic nanoparticles as a dispersant [10,11] . In principle, such hydrolytically degradable nanoparticles could be used to prepare more environmentally‐friendly next‐generation agrochemical formulations.…”
Section: Resultssupporting
confidence: 81%
“…Unfortunately, this precludes their use for this agrochemical application and is also problematic for other potential applications in personal care and cosmetics formulations. Nevertheless, in a follow‐up study we established the fundamental design rules for using nanoparticle dispersants in the context of various agrochemical compounds (including five fungicides and a pesticide) [10,11] . Bearing the latter results in mind, we decided to evaluate the new hydrolytically degradable PDMAC 30 ‐PCL 16 ‐PDMAC 30 nanoparticles as a dispersant for azoxystrobin.…”
Section: Resultsmentioning
confidence: 99%
“…The self-organizing behaviors of amphiphilic polymers have attracted considerable attention in polymer chemistry, , supramolecular chemistry, and biochemistry. Moreover, the application of amphiphilic polymers in the industry has recently become an important subject. For example, amphiphilic polymers have been utilized as dispersants of nanoparticles. Recent progress in the use of amphiphilic polymers can be found in the effective dispersion of colorants in aqueous media .…”
Section: Introductionmentioning
confidence: 99%
“…fundamental design rules for using nanoparticle dispersants in the context of various agrochemical compounds (including five fungicides and a pesticide). [10,11] Bearing the latter results in mind, we decided to evaluate the new hydrolytically degradable PDMAC 30 -PCL 16 -PDMAC 30 nanoparticles as a dispersant for azoxystrobin.…”
Section: Use Of Pdmac 30 -Pcl 16 -Pdmac 30 Nanoparticles In An Agroch...mentioning
confidence: 99%